The Positive Effect of Counseling about HIV-AIDS in High School - Agussalim, Agussalim; Nurmiaty, Nurmiaty; Ahmad, Aini; Reboldera, Melanie (Jurnal Bidan Cerdas, 2023)
Introduction: Adolescents constitute a significant demographic group susceptible to the development of the HIV/AIDS epidemic. The year 2020 witnessed a rise in the number of HIV/AIDS cases, with a notable concentration among individuals aged 20-29 years. Consequently, preventive measures should be targeted towards those under 20 years of age, specifically adolescents. This research aims to identify the impact of health counselling on teenagers’ knowledge of HIV/AIDS. Methods: The study utilizes a pre-experimental design, specifically a one-group pre-test and post-test design. The sample comprises 90 respondents selected through Simple Random Sampling. The research assesses the average knowledge level of teenagers before and after counselling, utilizing statistical analysis. Results: The findings indicate that the average knowledge level of teenagers before counselling is 1.49, whereas the average knowledge level after counselling is 1.94. The statistical analysis, employing the Wilcoxon Signed Rank Test, reveals a significant p-value of <0.001. Conclusion: The research concludes that health counselling has a substantial influence on enhancing teenagers' knowledge about HIV/AIDS. This underscores the importance of implementing targeted health interventions and educational programs to raise awareness and knowledge levels among adolescents, contributing to the overall prevention and control of HIV/AIDS in this vulnerable population.